2021
DOI: 10.1098/rsta.2020.0211
|View full text |Cite
|
Sign up to set email alerts
|

Collective knowledge: organizing research projects as a database of reusable components and portable workflows with common interfaces

Abstract: This article provides the motivation and overview of the Collective Knowledge Framework (CK or cKnowledge). The CK concept is to decompose research projects into reusable components that encapsulate research artifacts and provide unified application programming interfaces (APIs), command-line interfaces (CLIs), meta descriptions and common automation actions for related artifacts. The CK framework is used to organize and manage research projects as a database of such components. Inspired by the USB ‘plug and p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…For example, a new study on software artifacts in CS research observed that while artifact sharing rate is increasing, the bidirectional links between artifacts and papers do not always exist or last very long, as we have also found ( Hata et al, 2021 ). Some of the reasons that researchers struggle to reproduce experimental results and reuse research code from scientific papers are the continuously changing software and hardware, lack of common APIs, stochastic behavior of computer systems, and a lack of a common experimental methodology ( Fursin, 2021 ), as well as copyright restrictions ( Stodden, 2008 ).…”
Section: Related Workmentioning
confidence: 99%
“…For example, a new study on software artifacts in CS research observed that while artifact sharing rate is increasing, the bidirectional links between artifacts and papers do not always exist or last very long, as we have also found ( Hata et al, 2021 ). Some of the reasons that researchers struggle to reproduce experimental results and reuse research code from scientific papers are the continuously changing software and hardware, lack of common APIs, stochastic behavior of computer systems, and a lack of a common experimental methodology ( Fursin, 2021 ), as well as copyright restrictions ( Stodden, 2008 ).…”
Section: Related Workmentioning
confidence: 99%
“…That is, they provide a website for domain experts to search for a workflow which suits their needs 48 . We also point to the impressive Collective Knowledge framework [40] for a repository focusing on AI, ML, and system research 49 .…”
Section: Providing a Solution Workflow For A Ds And/or ML Problemmentioning
confidence: 99%
“…Os autores desse estudo apontam que a previsão eficaz de scripts de IaC propensos a falhas permite que metodologias de DevOps sejam aplicadas com enfoque nessa área, auxiliando na garantia de qualidade. Em A6, [Fursin 2021] propõe um framework para a organizac ¸ão de projetos de pesquisa como um banco de dados de componentes reutilizáveis e fluxo de dados automatizado. O artigo A7, de [García et al 2020], apresenta uma arquitetura distribuída para prover àqueles que trabalham com aprendizado de máquina ferramentas e servic ¸os de nuvem para a melhoria do processo de implantac ¸ão dos modelos.…”
Section: Respostas à Qp1unclassified